Creatine supplementation attenuates the rate of fatigue development during intermittent isometric exercise performed above end-test torque - Abdalla, Leonardo Henrique Perinotto [UNESP]; Broxterman, Ryan Michael; Greco, Camila Coelho [UNESP]; Denadai, Benedito Sergio [UNESP] (Wiley-Blackwell, 2020)
New Findings What is the central question of this study?Does creatine supplementation augment the total torque impulse accumulated above end-test torque (IET) during severe-intensity knee-extensor exercise by attenuating the rate of decrease in peak potentiated twitch torque (PT)? What is the main finding and its importance?Creatine augmented the IET and attenuated the rate of decrease in both voluntary activation and PT during severe-intensity exercise. The IET was related to the rate of decrease in PT. These findings reveal an important role for the rates of neuromuscular fatigue development as key determinants of exercise tolerance within the severe domain. This study investigated the effect of creatine supplementation on exercise tolerance, total torque impulse accumulated above end-test torque (total IET) and neuromuscular fatigue development of the knee extensors during severe-intensity intermittent isometric exercise. Sixteen men were randomly allocated into Creatine (n = 8, 20 g day(-1)for 5 days) or Placebo (n = 8) groups and performed knee-extensor maximal voluntary contraction (MVC) testing, all-out testing to determine end-test torque (ET) and the finite torque impulse accumulated above end-test torque (IETMODIFIER LETTER PRIME), and three submaximal tests at ET + 10%: (i) time to task failure without supplementation (Baseline); (ii) time to task failure after creatine or placebo supplementation; and (iii) time matched to Baseline after creatine (Creatine-Isotime) or placebo (Placebo-Isotime) supplementation. Creatine supplementation significantly increased the time to task failure (Baseline = 572 +/- 144 s versus Creatine = 833 +/- 221 s) and total IET (Baseline = 5761 +/- 1710 N m sversusCreatine = 7878 +/- 1903 N m s), but there were no significant differences within the Placebo group. The percentage change pre- to postexercise in MVC, voluntary activation, peak potentiated twitch torque and integrated EMG during MVC were not significantly different between Baseline and Creatine but were all significantly attenuated in Creatine-Isotime compared with Baseline. There were no significant differences in these variables within the placebo group. The total IET was significantly correlated with the rates of change in potentiated twitch torque peak (r = 0.83-0.87) and rate of torque development (r = -0.83 to -0.87) for the submaximal tests to task failure. These findings reveal an important role for the rates of neuromuscular fatigue development as key determinants of exercise tolerance during severe-intensity intermittent isometric exercise.
Keywords: central fatigue; exercise tolerance; peripheral fatigue; severe-intensity domain